Generalklausul mot skatteflykt - Rosander, Ulrika (Internationella Handelshögskolan, 2007)
Skatteflykt motverkas i många rättssystem genom åtgärder på olika nivåer. I Sverige är en av de metoder som används en lagstiftad generalklausul mot skatteflykt, skatteflyktslagen. Såväl rättssäkerhet som skattesystemets effektivitet anses vara grundläggande värden att upprätthålla i det svenska skattesystemet. Skatteflyktsproblematiken innebär dock att dessa båda värden i vissa situationer inte samtidigt kan uppfyllas fullt ut, vilket innebär att ett rättsligt område skapas där det blir nödvändigt att göra kompromisser och avvägningar. Det är den här balansen som är den stora utmaningen gällande åtgärder mot skatteflykt och som blir mycket tydlig gällande skatteflyktslagen. Avhandlingen analyserar generalklausuler mot skatteflykt ur ett rättssäkerhets- och effektivitetsperspektiv. Denna analys genomförs i form av en komparativ studie av Sveriges, Kanadas och Tysklands generalklausuler mot skatteflykt. Användandet av en generalklausul jämförs också med användandet av en praxismetod, vilket är den andra repressiva metoden mot skatteflykt som är frekvent förekommande i olika rättssystem världen över. Det konstateras att det är många olika frågor vid sidan av den konkreta rekvisitkonstruktionen och tillämpningsområdet som påverkar vilken rättssäkerhet och effektivitet som en generalklausul mot skatteflykt uppnår. Hur domstolssystemet ser ut, vilken inställning som finns till lagtolkning och hur domstolarna och skattemyndigheten väljer att tillämpa klausulen är exempel på mer generella frågor som har stor betydelse. Men även t.ex. relationen till andra metoder mot skatteflykt, möjligheten att erhålla förhandsbesked och vilka administrativa specialregler som används påverkar. I avhandlingen framför författaren sin uppfattning om vilka områden som är av störst vikt att utveckla i svensk rätt för att stärka skatteflyktslagens rättssäkerhet och effektivitet i framtiden.
Keywords: Fraude fiscale; Skatterätt; Tax fraud; Tax law

Licensavtalet och konkurrensrätten - Gölstam, Carl Martin (Uppsala universitet, 2007)
The purpose of this thesis is to describe and analyse the significance of economic thinking and arguments in the treatment of licence agreements in EC competition law. A central question is to what degree the concept of competition in EC law reflects an economically realistic approach to competition. The study also investigates to what degree the economic functioning of intellectual property is considered in competition regulation and how much the economic functioning of the licence agreement is considered. The investigation mainly consists of a comparative analysis of EC competition law and American antitrust law concerning the economic arguments and their importance. The treatment of territorial restrictions, field of use restrictions, quantity clauses, tie-outs, tie-ins, grant back, no-challenge clauses and price restrictions are of special interest here. This study shows that an economically realistic view of competition has influenced current EC competition law, especially in the Technology Transfer Block Exemption Regulation (TTBER). Exceptions from this development in the EC law are mainly due to the goal of integration of the common market. Territorial restrictions are strictly regulated in the TTBER even when the parties’ market shares are below the market thresholds defined in the regulation. The function of intellectual property rights are not much considered in EC competition law but there are general remarks about the economic functioning of patents in the Guidelines for the TTBER. However, it is difficult to find evidence for economic reasoning about patents in the formation of concrete rules. On the contrary, patents are weakened by the widened concept of exhaustion presented in the Guidelines. The economic functioning of the licence agreement is considered in the rules of TTBER and the economic arguments for clauses which create incentives for making investments or give the possibility of control are acknowledged. However, the free riding argument has a weak position when applied to territorial restrictions, which are more formalistically regulated. The EC competition law has become more similar to American antitrust law. The decisive difference consists in the judicial treatment of territorial restrictions, where the goal of integration is still of central importance in EC law.
Keywords: Antitrust Law; Civilrätt; Competencia; Competition law; Immaterialrätt; Intellectual property; Know-how; Konkurrensrätt; Law and Economics; Licence agreement; Licensavtal; Licensing; Patent; Private law; Rättsekonomi; Technology transfer; Tekniköverföring